Differences in performance indicators between winners and losers in senior inter county hurling championship. (4th July 2021) - O Brien, Paul; Martin, Denise; Bradley, Jonathan
ABSTRACT: Hurling is one of the oldest field sports in the world, yet little research has been conducted to develop our understanding of its game demands. This study aimed to create a profile of elite performance using data from three full seasons, and identify which performance indicators discriminate between winners and losers. A total of 77 Senior Inter County Hurling games (2018–2020) were analysed using NAC Sport Scout Plus, with all puckouts (5128), turnovers (6400) and shots (5695) coded. Paired sample t-tests and Wilcoxon signed rank testing were used to interrogate differences between winners and losers. Significant differences were identified in shooting indicators, with winning teams having higher total shot count (40), shot count from open play (29.5) and shot efficiency from both open play (61%) and dead balls (77%). There were significant differences in possession metrics; winners had a lower turnover rate (53%) and higher puckouts retention (65%), exhibiting higher overall productivity (3.8). These benchmark findings, and the detailed breakdown of puckout location and turnover type, will be of considerable interest to hurling coaches and analysts.